2008
DOI: 10.1111/j.1439-037x.2008.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Shoot and Root‐Zone Temperatures on Growth of Three Wheat Genotypes during Early Vegetative Stages

Abstract: Keywords high shoot/root-zone temperature; net assimilation rate; relative growth rate; specific root weight; wheat; xylem sap flow rate Correspondence I. AbstractHigh temperatures, whether of shoot or root, are reported to affect shoot and root growth of various plant species. The scanty information available on the differential response of wheat genotypes to high shoot and root-zone temperatures triggered this investigation to study the response and adaptation of shoot and root growth of three wheat genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
4
21
1
Order By: Relevance
“…Apparently, supra‐optimal temperatures can affect root growth at a higher extent as compared to shoot growth as observed in the current and other studies ( Tahir et al., ; Heckathorn et al., ). For example, many have reported that increasing the root‐zone temperature is more detrimental than increasing the ambient air temperature for root and shoot growth and that increasing the root‐zone temperature alone can result in inhibition of shoot growth (reviewed in Huang et al., ).…”
Section: Discussionsupporting
confidence: 76%
“…Apparently, supra‐optimal temperatures can affect root growth at a higher extent as compared to shoot growth as observed in the current and other studies ( Tahir et al., ; Heckathorn et al., ). For example, many have reported that increasing the root‐zone temperature is more detrimental than increasing the ambient air temperature for root and shoot growth and that increasing the root‐zone temperature alone can result in inhibition of shoot growth (reviewed in Huang et al., ).…”
Section: Discussionsupporting
confidence: 76%
“…1). Decrease of root weight and root/shoot ratio at high soil temperatures compared with control temperatures of 22-24ºC has been reported in other crops: grass at 35ºC (Xu and Huang, 2000a), wheat at 35ºC (Tahir et al, 2008) and tree of heaven (Ailanthus altissima) at 34ºC (Graves et al, 1991). The optimum soil temperature for root growth ranges from 10-18ºC in most cool-season grasses (Fly and Huang, 2004), and is about 20ºC in cucumbers (Tachibana, 1982).…”
Section: Root and Shoot Growthmentioning
confidence: 99%
“…In this study, root respiration, and uptake of water and nutrients might be stimulated by high soil temperature until 7 DAT. Inhibition of water uptake by long-term elevation of soil temperature was observed in tree of heaven (Graves et al, 1991) and wheat (Tahir et al, 2008); that of root respiration was observed in tomatoes (Klock et al, 1997). The nitrogen and water absorption in rice decreased by long-term elevation of water temperature at 37ºC (Baba, 1958).…”
Section: Photosynthetic Rate Non-structural Carbohydratementioning
confidence: 99%
See 1 more Smart Citation
“…PG without soil covering could not buffer the high root zone temperature, and consequently inhibited the growth and fruit yield of sweet pepper compared to other treatments due to high root zone temperature [30,31] . Previous studies showed that the effects of high root zone temperature on plants were more apparent than those of high air temperature [18,32] . For example, a high root zone temperature reduced the accumulation of dry matter and affected the growth of sweet pepper [33] .…”
Section: Discussionmentioning
confidence: 99%